Development and Design of PDI Perjuangan Membership Application Information System for Pasuruan Regency - Maghfudin, Rafly; Rahmawati, Yunianita (SAGA: Journal of Technology and Information System, 2025)
This research aims to develop and design a membership application information system for PDI Perjuangan Pasuruan Regency to improve the efficiency of member data management. By using the methodology of needs analysis, system design, and application development, this system is developed with PHP programming language and MySQL database. The result is an application that allows administrators to manage membership data effectively, including new member registration and member data search features. This application is expected to simplify administration and improve the quality of service to party members.